THE EFFECT OF DISCOVERY LEARNING MODEL ON STUDENTS' COGNITIVE IMPROVEMENT IN BIOLOGY MATERIAL OF X CLASS - Wigati, Indah; Aini, Kurratul; Yulekah, Siti; Agusta, Erie (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
Discovery learning model is one model that can increase student activity in the learning process so that students seek and find their own knowledge. This study aims to determine the effect of discovery learning model on the cognitive improvement of students on Biology material in X class. Research method used in this research is quasi experiment with research design of Non-equivalent Control Group Design. The population in the study consisted of 5 classes totaling 256 students. Sampling is used by using simple random sampling technique. The sample of this study is X MIA 1 class as experiment amounted to 37 and X MIA 3 class as the control class amounted to 45 students. In the learning process, the experimental class is treated by using discovery learning model and control class is taught with conventional model. The results of this study indicate that the average Ngain of the experimental class is 0.56 which is in the medium category and the average N-gain for the control class is 0.30 which belongs to the low category. Data analysis using t-test with significant level 0,05 obtained tarithmetic = 7,470 while t-table = 1,667 seen that t-arithmetic> t-table. This can be seen from the calculation of cognitive t-test showed students sig. t-arithmetic 0.000 <0,05, then Ha is accepted and H0 is rejected. The result of the analysis of the average increase of cognitive completeness of the experimental students. In the experimental class reaches 32.65% while the cognitive students in the control class is 12.42% which means that the cognitive of the experimental class is higher than the control class instudent's cognitive. Thus, it can be deduced that the Disccovery learning model has an effect on the students’ cognitive improvement on X class student biology material.